The Role Of Central Transfer Funds In Increasing The Impact Of Capital Expenditure And The Size Of Local Government On Regional Financial Performance In Java Island - Amanda Nurmubayani Permatasari; Raden Budi Hendaris (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
This study aims to analyze the role of central transfer funds in increasing the influence of capital expenditure and local government size on regional financial performance in districts/cities across Java for the period 2019–2023. A quantitative approach was applied using secondary data obtained from the Directorate General of Fiscal Balance (DJPK) and audited Local Government Financial Reports (LKPD) issued by the Supreme Audit Agency (BPK). Regional financial performance was measured using the fiscal independence ratio, capital expenditure was assessed through its proportion to total regional expenditure, and local government size was proxied by total assets. Data analysis was performed using panel data regression with the Moderated Regression Analysis (MRA) method. The results show that capital expenditure has a negative and insignificant effect on regional financial performance, while local government size shows a negative and significant effect. Central transfer funds are also found to have a negative and significant impact on performance. Furthermore, central transfer funds strengthen the relationship between local government size and financial performance but do not moderate the effect of capital expenditure. These findings highlight the need for more efficient capital management and strategic utilization of central transfers to enhance fiscal independence in Java.